Influence of a Putative ECF Sigma Factor on Expression of the Major Outer Membrane Protein, OprF, in Pseudomonas aeruginosa and Pseudomonas fluorescens - Brinkman, Fiona S. L. (American Society for Microbiology, 1999)
The gene encoding OprF, a major outer membrane protein in Pseudomonas species (formerly known as type 1 pseudomonads), was thought to be constitutively transcribed from a single sigma 70 promoter immediately upstream of the gene. We now report the identification of a novel putative ECF (extracytoplasmic function) sigma factor gene, sigX, located immediately upstream of oprF in both Pseudomonas aeruginosa PAO1 and Pseudomonas fluorescens OE 28.3 and show that disruption of this gene significantly reduces OprF expression. In P. aeruginosa, Northern analysis demonstrated that this reduction was a result of an effect on transcription of monocistronic oprF combined with a polar effect due to termination of a transcript containing sigX and oprF. Comparison of sigX-disrupted and wild-type cell transcripts by primer extension indicated that monocistronic transcription of oprF occurs from two overlapping promoters, one that is SigX-dependent and resembles ECF sigma factor promoters in its minus-35 region and another promoter that is independent of SigX and is analogous to the sigma 70-type promoter previously reported. Complementation of the P. aeruginosa sigX-disrupted mutant with plasmid-encoded OprF did not resolve the phenotypes associated with this mutant, which included a markedly reduced logarithmic-phase growth rate in rich medium (compared to that in minimal medium), further reduction of the growth rate in a low-osmolarity environment, secretion of an unidentified pigment, and increased sensitivity to the antibiotic imipenem. This indicates that SigX is involved in the regulation of other genes in P. aeruginosa. Disruption of the sigX gene in P. fluorescens also had an effect on the logarithmic-phase growth rate in rich medium. A conserved sigX gene was also identified in a Pseudomonas syringae isolate and six P. aeruginosa clinical isolates. Collectively, these data indicate that an ECF sigma factor plays a role in the regulation and expression of OprF and also affects other genes.